2020
DOI: 10.1177/2036361320960060
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases from Truncal and extremity bone and soft tissue sarcoma: Single institution study of oncologic outcomes

Abstract: Brain metastases are a rare occurrence in patients with sarcoma. The prognosis for patients is poor, and treatment can contribute to considerable morbidity. We sought to examine the experience of our institution in managing these patients over a period of 17 years. We performed a retrospective cohort study of patients managed for sarcoma of the extremity or trunk who developed brain metastases from 2000 to 2017. Clinical data were analyzed and we assessed survival outcomes. 14 patients presenting at a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…In accordance with our findings, studies show that most patients with BM had a lower limb primary tumor, 5 , 10 with most being localized to the thigh. 10 In addition, we encountered that patients with BM tended to have larger primary tumors with 27.3% being >15 cm in their greatest dimension (T4 stage).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with our findings, studies show that most patients with BM had a lower limb primary tumor, 5 , 10 with most being localized to the thigh. 10 In addition, we encountered that patients with BM tended to have larger primary tumors with 27.3% being >15 cm in their greatest dimension (T4 stage).…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of patients with BM in this study was 49.5 years. This value falls between the mean age reported by Salvati et al 7 (33.1 years) and Chan et al 5 (56.6 years). Both of these studies also demonstrated a male predominance unlike ours (59.1% of patients with BM were women).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, retroperitoneal STSs also tend to metastasize to the liver [14,15]. Other metastatic sites commonly include the bones and the brain [16,17]. Patients with STSs are managed according to the generally accepted guidelines and those with localized and resectable diseases are treated by surgery [18].…”
Section: Introductionmentioning
confidence: 99%